Sintesa Karbon Aktif dari Kulit Salak dengan Aktivasi Kimia-Senyawa ZnCl2 dan Aplikasinya pada Adsorpsi Zat Warna Metilen Biru - Raymond Tanumiharja (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Microporous mesoporous activated carbon derived from salacca peel with surface area as high as 1435,76 m2/g has been successfully synthesized with Zinc Chloride (ZnCl2) as an activating agent. Salacca peel was firstly impregnated with fixed zinc chloride to salacca peel mass ratio of 2:1 and with fixed zinc chloride concentration of 20%-w. The impregnated salacca peel was pyrolized at 700°C in nitrogen atmosphere. The adsorption capability of the activated carbon was investigated by using methylene blue (MB) as dye. The adsorption study was realized in batch reactor with various MB initial concentrations of 2, 4, 6, 8, and 10 ppm. Langmuir, Tempkin, Freundlich, and Dubinin-Radushkevich isotherm models were used for mathematical description of the adsorption equilibrium. It was found that the equilibrium concentrations of the adsorption fitted very well with monolayer Langmuir isotherm model, with maximum adsorption capacity of 387,38 mg. g-1. The kinetic study was performed based on pseudo-first-order, pseudo-second-order, and intraparticle diffusion equations. The data indicated that the adsorption kinetics followed the pseudo-secondorder mechanism closely than the pseudo-first-order and the intraparticle diffusion mechanism. The present study concludes that activated carbon derived from salacca peel could be employed as a potential adsorbent for the removal of color and dyes from aqueous solution, MB in particular.